2022
DOI: 10.1177/00084174221132097
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Suicide Safety Planning Interventions: A Systematic Review Informing Occupational Therapy

Abstract: Background. Suicide safety planning (SSP) is a suicide prevention approach that involves developing a collaborative plan between a service provider such as an occupational therapist and a person who is at risk of suicide. Purpose. To synthesize effectiveness studies on SSP. Method. Using the Joanna Briggs Institute methodology, we conducted a systematic review of effectiveness studies including a: (1) title and abstract screening; (2) full-text review; (3) critical appraisal; and (4) narrative synthesis. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 76 publications
0
2
0
2
Order By: Relevance
“…Overall, our findings suggest that interventions aimed at engaging individuals in meaningful activity are a serious gap in existing services. In a recent systematic review focused on the effectiveness of interventions for engaging individuals experiencing homelessness in meaningful activity, only nine moderate-high quality studies were identified [ 65 ]. The dire lack of intervention research in this area combined with the findings of this study suggest that future research aimed at developing and evaluating such interventions is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings suggest that interventions aimed at engaging individuals in meaningful activity are a serious gap in existing services. In a recent systematic review focused on the effectiveness of interventions for engaging individuals experiencing homelessness in meaningful activity, only nine moderate-high quality studies were identified [ 65 ]. The dire lack of intervention research in this area combined with the findings of this study suggest that future research aimed at developing and evaluating such interventions is needed.…”
Section: Discussionmentioning
confidence: 99%
“…En plus des articles qui ont été spécifiquement soumis en lien avec le thème, on trouve dans ce numéro spécial une revue systématique sur l’efficacité des interventions de planification en prévention du suicide (Marshall, Crowley, et al, 2023), une contribution importante pour aider les ergothérapeutes à mieux soutenir les personnes présentant un risque de suicide. Cet article synthétise 22 études, dont trois sur des interventions de planification en prévention du suicide intégrant les occupations significatives.…”
unclassified
“…Dans « Activité significative, bien-être psychosocial et pauvreté pendant la COVID-19 : une étude longitudinale » (« Meaningful activity, psychosocial well-being, and poverty during COVID-19: A longitudinal study »), Marshall, Gewurtz et leurs collaborateurs (2023) cherchent à comprendre comment les politiques de distanciation physique ont entraîné une diminution de la participation à des activités significatives chez les personnes en situation de pauvreté et exacerbé les iniquités à travers une étude réalisée sur une période d’un an. Les participants ont perdu l’accès à des installations favorisant les occupations actives et créatives, ce qui les a laissés isolés et avec trop de temps libre.…”
unclassified
See 1 more Smart Citation